Strength and compressibility behavior of soil treated with palm oil fuel ash-based geopolymer - Soliman, Khasib Isam Adnan (2021)
The use of geopolymer in soil stabilization has gained much attention recently due to its efficiency in improving the engineering properties of soils and being environmentally friendly at the same time. Common binders such as cement and lime yield in high stabilization potential but they were found to be uneconomical and contributed to some environmental issues. Hence, this research aimed to investigate the effect of palm oil fuel ash (POFA) based geopolymer on soft soil stabilization. The geopolymer was synthesized from POFA and an alkaline activator solution which was made from a mixture of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) at ambient temperature. The mechanical and microstructural behavior of two types of clayey soils stabilized with POFA-based geopolymer at four dosages (G10PA, G20PA, G30PA and G40PA) were investigated in this study. In this respect, a series of unconfined compression (UCS), one-dimensional consolidation, direct shear and California Bearing Ratio (CBR) tests was conducted to investigate the mechanical properties of soils treated with POFA-based geopolymer. The microstructural changes and mineralogy of the treated samples were analyzed by Field Emission Scanning Electron Microscopy along with Energy Dispersive X-Ray (FESEM-EDX) and X-Ray Diffraction (XRD) analyses. Furthermore, the physical properties of soils (Atterberg Limits, Plasticity Index, and Linear Shrinkage Limit), pH and compaction assessment were investigated before and after treatment with POFA-based geopolymer. The results indicated that shear strength and compressibility of both soils increased and decreased respectively by increasing the dosage of POFA-based geopolymer. Geopolymer with 40% POFA of the dry weight of soils (G40PA) yielded the highest UCS values and; least permeability and compressibility. Compressive strength of untreated soil 1(S1) and soil 2 (S2) increased from 0.26 MPa and 0.13 MPa reaching 4.18 MPa and 2.86 MPa for S1-G40PA and S2-G40PA, respectively. The permeability coefficient of S1 and S2 stabilized with G40PA is almost 300% and 200% smaller than that of the untreated samples, respectively. The potentiality of compressibility of natural S1 is considerably reduced from medium to a low level after geopolymer stabilization whereas S2 reduced from high to a medium level. In addition, it was observed that the longer the curing period (28 days) of the stabilized soils, the higher the compressive strength of the soil developed. However, the microstructural analysis (FESEM-EDX) revealed the material modifications can be related to the strength behavior in which geopolymer gel filled the interparticle voids in which a stiff soil structure was noticed. FESEM-EDX analysis has proved that geopolymer gel binding effect contributed to the improvement in the mechanical properties of stabilized soils. New minerals were found in the treated samples such as mullite and augite which are associated with geopolymerization reaction as indicated by XRD results. These results suggest the potentiality of using POFA-based geopolymer binder to stabilize soft soil.